Unsteady Aerodynamic Forces of Tandem Flapping Wings with Different Forewing Kinematics - Zengshuang Chen; Yuxin Xie; Xueguang Meng (Biomimetics)
Dragonflies can independently control the movement of their forewing and hindwing to achieve the desired flight. In comparison with previous studies that mostly considered the same kinematics of the fore- and hindwings, this paper focuses on the aerodynamic interference of three-dimensional tandem flapping wings when the forewing kinematics is different from that of the hindwing. The effects of flapping amplitude (Φ1), flapping mean angle (<semantics><mover accent="true">ϕ1¯</mover></semantics>), and pitch rotation duration (Δtr1) of the forewing, together with wing spacing (L) are examined numerically. The results show that Φ1 and <semantics><mover accent="true">ϕ1¯</mover></semantics> have a significant effect on the aerodynamic forces of the individual and tandem systems, but Δtr1 has little effect. At a small L, a smaller Φ1, or larger <semantics><mover accent="true">ϕ1¯</mover></semantics> of the forewing can increase the overall aerodynamic force, but at a large L, smaller Φ1 or larger <semantics><mover accent="true">ϕ1¯</mover></semantics> can actually decrease the force. The flow field analysis shows that Φ1 and <semantics><mover accent="true">ϕ1¯</mover></semantics> primarily alter the extent of the impact of the previously revealed narrow channel effect, downwash effect, and wake capture effect, thereby affecting force generation. These findings may provide a direction for designing the performance of tandem flapping wing micro-air vehicles by controlling forewing kinematics.